Prevalence rate of placenta accreta in women candidates for non-emergency cesarean section with previous cesarean section referred to Tabriz Women's Hospitals: 2012-2016 - Fatemeh Abasalizadeh; Shamsi Abasalizadeh; Ladan Kalafi (Mashhad University of Medical Sciences, 2020)
Introduction: Lack of knowledge about the prevalence of placenta accreta causes unintended complications in susceptible women. Awareness of its prevalence can guarantee the diagnostic and therapeutic methods in susceptible women in future studies. This study was performed with aim to evaluate the prevalence rate of placenta accreta in women candidate for non-emergency cesarean section with previous cesarean section referred to Tabriz women's hospitals. Methods: This descriptive-analytical study was performed during 2012-2016 at Tabriz two hospitals of Al-Zahra and Taleghani with the participation of 310 women candidate for non-emergency cesarean. The individual information including demographic characteristics and disease-related information was included in the researcher-made checklist. Data were analyzed using SPSS software (version 20) and Spearman correlation and regression tests. PResults: 55 patients (17.74%) had placenta accreta; the variables such as age (P=0.001), BMI (P=0.003), number of previous cesarean section (P=0.002), cigarette smoking (P=0.036), number of previous pregnancies (P=0.002), history of myomectomy (P=0.001), third trimester hemorrhage (P=0.003), and number of baby during delivery (P=0.003) were significantly associated with placenta accreta. Conclusion: The prevalence of placenta accreta was 17.74% in the present study, which necessitates doing precise diagnostic measures to be aware of this complication.